Research on ordered Boolean expression matching with window - CAO Jing1; LIU Yan-bing1; LIU Ping1; TAN Jian-long1; GUO Li1 (Tongxin xuebao)
In view of the difficulty of the complex rule matching problem,Boolean expression matching and a algorithm framework were proposed to solve it.Two popular methods above this framework were given.In addition,two parame-ters-ORDER and WINDOW-were added into Boolean expression matching in order to enhance the power of the expres-sion rule.Then BitCountOWBE algorithm was proposed under these two parameters.Test results indicated that Bit-Count-OWBE could resolve the complex rules matching problem on the scale of 10 000 with no performance decline in most cases.